PENGARUH BELANJA LANGSUNG APBD DAN APBN TERHADAP INDEKS KEPUASAN MASYARAKAT (IKM) DENGAN VARIABEL INTERVENING PENCAPAIAN INDIKATOR KINERJA UTAMA (IKU) : STUDI PADA PUSKESMAS KABUPATEN MADIUN - Vitanto, Bagus Rahmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Aims of this research to examine influence of local government direct expenditure and central government direct expenditure to society satisfaction index with key performance indicator as intervening variable. Society satisfaction index measured by distribute questionnaire to society about Puskesmas services. Population on this research are all of Madiun Regency’s Puskesmas used direct expenditure and reported accession key performance indicator and society satisfaction index from 2012 to 2014. The Result of this research indicate local government direct expenditure have positive influence on key performance indicator, central government direct expenditure haven’t influence on key performance indicator, key performance indicator have positive influence on society satisfaction index, local government direct expenditure haven’t direct influence on society satisfaction index, central government direct expenditure haven’t direct influence on society satisfaction index, but the local government direct expenditure have indirect influence on society satisfaction index with key performance indicator as variable intervening. Key word : local government direct expenditure, central government direct expenditure, society satisfaction index, key performance indicator